FIGURATIVE LANGUAGE USED IN JOHN DRYDEN'S POETRY HAPPY THE MAN - Cristiana, Olga (ELite Journal : International Journal of Education, Language and Literature, 2023)
One of the elements in poetry is the use of figurative language. This study identifies the types of figurative language used in John Dryden’s Happy the Man. This study used textual analysis, and the present study revealed that the poem used five kinds of figurative languages, namely metaphor, synecdoche, irony, personification, and symbol. Every figurative language in this poem conveys a deep meaning about human life. These figurative languages provide the poem with the device to use limited number of words to convey multiple layers of meaning.